Aux deux extrémités d’une route transnationale : spatialiser les marchés transnationaux entre l’Algérie et la Chine - Saïd Belguidoum; Olivier Pliez (M@ppemonde)
This article proposes a socio-spatial approach to transnational trade by focusing on two trading posts situated at either end of the transnational route between Algeria and China: El Eulma and Yiwu. These two marketplaces, located in separate geographical contexts, are interconnected by discreet and efficient dynamics and are indicative of the processes in which transnational markets operate and evolve. When considered together as a whole, El Eulma and Yiwu provide insight into the way one market echoes another within a global relational system. The study of these two marketplaces demonstrates that the understanding of Inconspicuous Globalisation involves the local scale and not solely the national one. The article is based on a series of sociological and urban geographical surveys conducted jointly or separately between 2009 and 2016.